Insight to physiology and pathology of zinc(II) ions and their actions in breast and prostate carcinoma - Gumulec, J; Masarik, M; Krizkova, S; Adam, V; Hubalek, J; Hrabeta, J; Eckschlager, T; Stiborova, M; Kizek, R (Current medicinal chemistry, 2011)
Zinc(II) ions contribute to a number of biological processes e.g. DNA synthesis, gene expression, enzymatic catalysis, neurotransmission, and apoptosis. Zinc(II) dysregulation, deficiency and over-supply are connected with various diseases, particularly cancer. 98 % of human body zinc(II) is localized in the intracellular compartment, where zinc(II) is bound with low affinity to metallothionein (MT). Zinc transporters ZIP and ZnT maintain transmembrane transport from/to cells or organelles. Imbalance of their regulation is described in cancers, particularly prostate (down-regulated zinc transporters ZIP1, 2, 3 and ZnT-2) and breast, notably its high-risk variant (up-regulated ZIP6, 7, 10). As a result, intracellular and even blood plasma zinc(II) levels are altered. MT protects cells against oxidative stress, because it cooperates with reduced glutathione (GSH). Recent studies indicate elevated serum level of MT in a number of malignancies, among others in breast, and prostate. MT together with zinc(II) affect apoptosis and proliferation, thus together with its antioxidative effects it may affect cancer. To date, only little is known about the influence of zinc(II) and MT on cancer, while these compounds may play an important role in pathogenesis. This review concludes current data regarding the impact of zinc(II) on the pathogenesis of breast and prostate cancers with potential outlines of new, targeted therapy and prevention. Moreover, blood plasma zinc(II) and MT levels and dietary zinc(II) intake are discussed in relation to breast and prostate cancer risk.
Keywords: metalothionein; Carrier Proteins; Metallothionein; sulfhydrylové sloučeniny; zinek; Male; Prostatic Neoplasms; lidé; Female; nádory prsu; ženské pohlaví; mužské pohlaví; Sulfhydryl Compounds; Breast Neoplasms; Humans; transportní proteiny; Zinc; nádory prostaty